2017
DOI: 10.1103/physrevc.95.011601
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of fusion on isospin dynamics

Abstract: We introduce a new microscopic approach to calculate the dependence of fusion barriers and cross-sections on isospin dynamics. The method is based on the time-dependent Hartree-Fock theory and the isoscalar and isovector properties of the energy density functional (EDF). The contribution to the fusion barriers originating from the isoscalar and isovector parts of the EDF is calculated. It is shown that for non-symmetric systems the isovector dynamics influence the sub-barrier fusion cross-sections. For most sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 70 publications
3
48
0
Order By: Relevance
“…Very little average proton transfer occurs after 48 Ca+ 132 Sn in agreement with Ref. [34], perhaps because the N/Z ratio of 132 Sn is much higher and is a closer match to the heavier calcium nuclei. It was found that subbarier fusion is enhanced for 40 Ca+ 132 Sn more than what can be accounted for by vibrational states [71].…”
Section: Transfer Effectssupporting
confidence: 87%
See 2 more Smart Citations
“…Very little average proton transfer occurs after 48 Ca+ 132 Sn in agreement with Ref. [34], perhaps because the N/Z ratio of 132 Sn is much higher and is a closer match to the heavier calcium nuclei. It was found that subbarier fusion is enhanced for 40 Ca+ 132 Sn more than what can be accounted for by vibrational states [71].…”
Section: Transfer Effectssupporting
confidence: 87%
“…In Ref. [34], the isovector contribution to the DC-TDHF fusion potentials for 40,48,54 Ca+ 132 is also related to neutron transfer, compatible with the directions in Fig. 5 and the resulting TDHF fusion barriers in Fig.…”
Section: Transfer Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…Recent TDHF studies have been performed to investigate the charge equilibration in deep-inelastic collisions [46,48] and its impact on the interplay between fusion and transfer reactions [49][50][51][52][53][54]. Recent investigations have also shown that the one-body dissipation mechanisms included in TDHF were the most relevant to describe fully damped reactions such as quasi-fission [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Note also that, once dynamics is included, fusion in these systems may behave differently and static effects on the bare potential could be washed out by the dynamics [33]. In particular, fusion in the 40 Ca+ 48 Ca system is expected to be strongly affected by transfer channels [40,46], a feature which has only recently been studied in microscopic approach [47].…”
mentioning
confidence: 99%